The Dynamics of Islamic Values and Korean Drama Romanticism in Shaping Gen Z Muslim Women's Life Partner Preferences - Mumtazah, Jihan; Kumaini, Ruston (Al-Fikru: Jurnal Ilmiah, 2026)
This study aims to analyze the dynamics of Islamic values and representations of romanticism in Korean dramas as they relate to the partner preferences of Generation Z Muslim women. The study employs a descriptive qualitative approach, involving eight Muslim women aged 18–29 who actively watch romantic Korean dramas. Data were collected via an open-ended online questionnaire and analyzed using thematic analysis through the stages of open coding, categorization, theme identification, and interpretation of meaning. Data credibility was ensured through source triangulation and member checking. The results indicate that romance in Korean dramas is primarily interpreted as a reflection of healthy relationship qualities, including emotional maturity, supportive communication, responsibility, empathy, and a sense of security. The formation of partner preferences occurs through a process involving media exposure, internalization, evaluation, value negotiation, and preference reconstruction. The findings also indicate that the influence of Korean dramas is not deterministic. Informants actively select values they consider aligned with the principles of Islamic Family Law—such as religion, morality, responsibility, and respect for one’s partner—while rejecting values that conflict with Sharia. This study confirms that preferences for a life partner result from a negotiation between media representations, individual experiences, and Islamic values.